Systematic Mapping Study: Strategic Entrepreneurship in MSME Business Development - Waliyyan, Urfan; Purbasari, Ratih; Purnomo, Margo (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
Micro, Small, and Medium Enterprises (MSMEs) have an important role in driving the economy in Indonesia. However, in the dynamic business development and technological developments that occur, to survive in the flow of business competition, the right strategy pattern is needed, to maintain existence in competition and business development. This study aims to provide an overall picture of the results of systematic mapping from strategic entrepreneurship studies based on articles obtained from the Scopus electronic database. This research is a secondary study using the systematic mapping study (SMS) method. Based on the results of systematic mapping, provides findings that the number of publications on strategic entrepreneurship studies is still small and has not varied in its development. The publication of strategic entrepreneurship only started in 2001 as many as 1 scientific article, the highest increase occurred in 2019 and 2020 as many as 6 articles each. The country that dominates the publication is Europe, namely France. The most widely used approach is the quantitative approach with survey methods. The type of research studied is evaluation research with the most focus being small-medium firms, namely MSME actors who are defined as organizations that have the potential to develop sustainably. This research can be useful for academics and practitioners as a first step in conducting research on strategic entrepreneurship and in setting this strategy for MSME actors for business development which ultimately can also help the country's economy.